Eksistensi Spiritualitas Guru Pendidikan Islam dalam Pembinaan Kompetensi Kepribadian - Budiman, Budiman (IAIN Ponorogo, 2016)
Abstract: The perspective of Islamic education provides clearinsight that the existence of teacherspirituality is the actualization of Nafsiahpowers (al-aql, al-qalb and al-nafs) and spiritual (al-ruh and al-fitrah) on a variety of educational activities. Islamic education teachers are often recognized as having good personalities such ascaring, graceful, tawÃ¢du, and wise, giving convenience, rehearsing the learning process, exemplifying a practice, providing punishment for guidance, giving forgiveness and praise.The study of the existence of Islamic education teacher spirituality has confirmed the relevance of teacher spirituality in coaching the teachers personality competence. The actualization of teacher spirituality can be seen from the characteristics of Islamic education teachers as muallim/Ustaz, murabbi, muaddib, mudarris, mursyid, whohaveintegrity such as scholarly, attitudes and behavior patterns in the implementation of the duties and responsibilities of education. Teacher spirituality potential can be known by the proper resources that must be seen from al-Quran and Sunnah, as well as thought of both classical and contemporary Islamic educationleaders.Ø£Ø´Ø§Ø±Øª Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø¥ÙÙ Ø£Ù Ø±ÙØØ§ÙÙØ© Ø§ÙÙ Ø¯Ø±ÙØ³ ÙÙ Ø£ÙØ´Ø·Ø© Ø§ÙÙÙÙ Ø§ÙÙÙØ³ÙØ© (Ø§ÙØ¹ÙÙ ÙØ§ÙÙÙØ¨ ÙØ§ÙÙÙØ³) ÙØ±ÙØØ§ÙÙØ© Ø§ÙØ±ÙØ ÙØ§ÙÙØ·Ø±Ø© ÙÙ ÙØ«ÙØ± Ù Ù Ø§ÙØ£ÙØ´Ø·Ø© Ø§ÙØªØ±Ø¨ÙÙØ©. ÙÙØ§Ù Ø£Ø´ÙØ§Ù Ù Ù Ø³ÙÙÙÙÙØ§Øª Ù Ø¯Ø±Ø³ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙÙ Ø¹ØªØ±Ù Ø¨Ø§ÙÙ Ø¯Ø±Ø³ Ø°Ù Ø´Ø®ØµÙØ© Ø¬ÙÙØ¯Ø© ÙÙ Ø§ÙÙ Ø¯Ø±ÙØ³ Ø§ÙÙ ØªØµÙ Ø¨Ø§ÙØ±ØÙ Ø©Ø ÙØ§ÙØÙÙ Ø ÙØ§ÙØµØ¨Ø± ÙØ§ÙØªÙØ§Ø¶Ø¹Ø ÙØ§ÙØÙÙ Ø©Ø ÙØ§ÙÙ Ø³ÙÙÙØÂ ÙØ§ÙÙ ÙØ±ÙØ± ÙÙ Ø£Ø¯Ø§Ø¡ Ø§ÙØªØ¯Ø±ÙØ³Ø ÙÙØ£ØªÙ Ø¨Ø§ÙÙ Ø«Ø§Ù ÙÙ Ø§ÙØ¹Ù ÙØ ÙÙØ£ØªÙ Ø¨Ø§ÙØ¹ÙØ§Ø¨ ØªØ£Ø¯ÙØ¨Ø§Ø ÙÙØªØµÙÙ ÙØ°ÙÙ Ø¨Ø§ÙØ¹ÙÙ ÙØ§ÙØÙ Ø¯.Â ÙØ¥Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙÙØ§Ø¦Ù Ø©Â ØªØ¬Ø§Ù ÙØ¬ÙØ¯ Ø±ÙØØ§ÙÙØ© Ù Ø¯Ø±ÙØ³ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ØªØ¤ÙÙØ¯ ÙØ¬ÙØ¯ Ø£ÙÙ ÙØ© Ø±ÙØØ§ÙÙØ© Ù Ø¯Ø±Ø³ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø¶ÙØ¡ ØªØ±ÙÙØ© Ø§ÙÙÙØ§ÙØ© Ø§ÙØ´Ø®ØµÙØ© ÙÙÙ Ø¯Ø±ÙØ³. ÙÙØ¬ÙØ¯ ÙØ°Ù Ø§ÙØ±ÙØØ§ÙÙØ© ÙØªÙ Ø«ÙÙ ÙÙ Ù Ù ÙÙØ²Ø§Øª Ù Ø¯Ø±ÙØ³ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙÙ ÙÙ ÙÙÙÙ Ù Ø¹ÙÙÙ Ø§/Ø£Ø³ØªØ§Ø°Ø§Ø ÙÙ Ø±Ø¨ÙÙØ§Ø ÙÙ Ø¤Ø¯ÙØ¨Ø§Ø ÙÙ Ø¯Ø±ÙØ³Ø§Ø ÙÙ Ø±Ø´Ø¯Ø§ Ø°Ø§ Ø´Ù ÙÙÙÙØ© Ø¨ÙÙ Ø§ÙØ¹ÙÙ ÙÙØ© ÙØ§ÙØ³ÙÙÙÙØ© ÙÙ Ø£Ø¯Ø§Ø¡ ÙØ¸ÙÙØªÙ Ø§ÙØªØ±Ø¨ÙÙØ©.Â ÙÙØ°Ù Ø§ÙØ±ÙØØ§ÙÙØ© ÙÙÙ Ø¯Ø±Ø³ Ø¹ÙØ±ÙØª Ù Ù Ø§ÙÙ ØµØ§Ø¯Ø± Ø§ÙÙ ÙØ§Ø³Ø¨Ø©Ø ÙÙØ¬Ø¨ Ø£Ù ØªÙØ¨Ø¹ Ù Ù Ø§ÙÙØ±Ø¢Ù ÙØ§ÙØ³ÙØ© ÙØ£ÙÙØ§Ø± Ø§ÙØ¹ÙÙ Ø§Ø¡ ÙØ§ÙØ®Ø¨Ø±Ø§Ø¡ ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙØ¯ÙÙ Ø§ ÙØØ¯ÙØ«Ø§.